Linkage studies of a Missouri kindred with autosomal dominant spondyloepimetaphyseal dysplasia (SEMD) indicate genetic heterogeneity. - Gertner, J; Whyte, M; Dixon, P; Pang, J; Trump, D; Pearce, S; Wooding, C; Thakker, R (1997)
A four-generation kindred (14 affected and 10 unaffected members) from Missouri, U.S.A. in which spondyloepimetaphyseal dysplasia (SEMD) had been inherited as an autosomal dominant disorder was investigated for linkage to 13 candidate loci: COL2AI, COL9AI, COL9A2, COL9A3, COL10A1, COL11A1, COL11A2, PSACH, FGFR3, decorin, CRTL1, COMP, and PTHRP. Mutations of COL2A1, COL9A2, COL10, and FGFR3 have been reported previously in the Strudwick type of SEMD, multiple epiphyseal dysplasia type 2 (EDM2), the Schmid type of metaphyseal dysplasia, and in achondroplasia, respectively, and the pseudoachondroplasia (PSACH) locus has been mapped to chromosome 19p12. In addition, mutations in COL9 and COL11A are associated with murine forms of degenerative joint disease and chondroplasia, respectively. The family proved informative for 12 of the 13 loci and was uninformative at the decorin locus. Linkage between this form of SEMD, designated the Missouri variant, SEMDMO, and the 12 informative candidate loci was excluded (LOD scores < -2.00 at theta = 0.005 to 0.15), thereby indicating further genetic heterogeneity in these inherited disorders of bone and cartilage development.